A Critical Study of Abdullahi Ahmed An-Na'im's Thought on Islamic Law Reform - Musadad, Ahmad; Syamsi, Ahmad Badarus; Baihaqi, Baihaqi; Khazin, A. Mufti; Pujiati, Tri (Nuris Journal of Education and Islamic Studies, 2025)
This study aims to critically analyze Ahmed An-Na’im’s thoughts in the renewal of Islamic law, which offers a new perspective on sharia as a dynamic interpretation of sacred texts. The urgency of this study lies in the need to understand the contextual approach to sharia in facing the challenges of modernity, especially in relation to Human Rights (HAM) and constitutionalism. This study uses a qualitative method with a literature study approach, which focuses on An-Na’im’s main works and relevant secondary literature. Data analysis was carried out through the content analysis method to identify patterns, themes, and implications of An-Na’im’s ideas. The results of the study show that An-Na’im defines sharia as an interpretation of texts that are equivalent to Islamic jurisprudence and law, not something sacred and static. His thoughts underline the relevance of sharia to the development of the times through the distinction between universal Makkiyah sharia and contextual Madaniyyah sharia. This idea is influenced by the nasakh theory of his teacher, Mahmoud Muhammad Thaha. However, An-Na’im’s approach has been criticized for being too focused on modern standards such as human rights, giving the impression that Islam needs to adapt to Western values. This study contributes to the discourse on Islamic legal reform by showing how An-Na’im’s approach opens up new interpretative space that remains relevant without ignoring the essence of justice in Islamic teachings